Aplicación de un sistema de costos por órdenes específicas y su incidencia en la gestión de la empresa Limpsa Servicios Generales SAC - año 2015 - Terrones Alfaro, Martha Jacqueline (2017)
The purpose of the present investigation is to determine if the application of a system of costs by specific orders influences the improvement of the management of the company Limpsa Servicios Generales SAC of the city of Trujillo year 2015; with the purpose of solving the deficiencies in the identification and control of the elements of the cost for each order of service; In addition to expressing the importance that it has in allowing the improvement of the decision making and also, to generate greater profits to the company. The type of research is descriptive, since the data are obtained directly from reality, whose information has been analyzed and structured as required. The population is determined by the cleaning service company Limpsa Servicios Generales SAC, registered in the Chamber of Commerce of La Libertad, the sample chosen for our investigation is the work order for the client Los Conquistadores Hotel SAC and the directed work order To a natural person, during the month of July 2015. By means of the results obtained in the application of the system of costs by specific orders, the company Limpsa Servicios Generales SAC, reduced its costs of sale in the orders of work N ° 1 and N ° 2, increasing its margin of operational utility of the month of July 2015; In addition to optimizing the use of its resources; Which guides the making of good decisions and the improvement of their management. Therefore, it is recommended to implement a cost system in the company Limpsa Servicios Generales SAC to control the identification of its costs and improve the company's performance.